Benign Hand Tumors (Part II): Soft Tissue Tumors. (May 2022) - Lans, Jonathan; Yue, Kai-Lou C.; Castelein, René M.; Suster, David I.; Petur Nielsen, G.; Chen, Neal C.; Lozano-Calderon, Santiago A.
Background: Benign soft-tissue tumors of the hand are more common than both their benign bone and malignant soft-tissue counterparts. This study evaluates the characteristics and treatment of benign soft tissue tumors in light of 1 institution's experience.Methods: Histologically confirmed benign soft-tissue tumors of the hand were retrospectively identified using International Classification of Disease codes from 1992 to 2015. A medical chart review was conducted to collect patient demographics, tumor epidemiology, and treatment.Results: A total of 199 soft-tissue tumors were identified. The median patient age at time of treatment was 47.4 ± 14.7 years in age. The majority of tumors were located in the digits (n = 168, 84%) and treated by excision (n = 191, 96%). Localized type tenosynovial giant cell tumors (n = 71, 36%) were the most common and had the highest rates of recurrence (8.5%) in this series. Other frequent histologies included hemangioma, schwannoma, and glomus tumors.Conclusion: Awareness and understanding of tumor characteristics may help physicians with diagnosis and treatment. There is an extensive variety of tumors, but the principles of clinical and imaging diagnosis are common to all of them. Marginal excision for the treatment pain, improvement of function, and cosmetic correction applies to all these tumors independent of the histology.